Robotic assisted laparoscopic partial nephrectomy using contrast‐enhanced ultrasound scan to map renal blood flow. Issue 1 (7th March 2016) - Alenezi, Ahmad; Motiwala, Aamir; Eves, Susannah; Gray, Rob; Thomas, Asha; Meiers, Isabelle; Sharif, Haytham; Motiwala, Hanif; Laniado, Marc; Karim, Omer
Abstract: Objective: The paper describes novel real‐time 'in situ mapping' and 'sequential occlusion angiography' to facilitate selective ischaemia robotic partial nephrectomy (RPN) using intraoperative contrast enhanced ultrasound scan (CEUS). Materials and methods: Data were collected and assessed for 60 patients (61 tumours) between 2009 and 2013. 31 (50.8%) tumours underwent 'Global Ischaemia', 27 (44.3%) underwent 'Selective Ischaemia' and 3 (4.9%) were removed 'Off Clamp Zero Ischaemia'. Demographics, operative variables, complications, renal pathology and outcomes were assessed. Results: Median PADUA score was 9 (range 7–10). The mean warm ischaemia time in selective ischaemia was less and statistically significant than in global ischaemia (17.1 and 21.4, respectively). Mean operative time was 163 min. Postoperative complications (n = 10) included three (5%) Clavien grade 3 or above. Malignancy was demonstrated in 47 (77%) with negative margin in 43 (91.5%) and positive margin in four (8.5%). Long‐term decrease in eGFR post selective ischaemia robotic partial nephrectomy was less compared with global ischaemia (four and eight, respectively) but not statistically significant. Conclusions: This technique is safe, feasible and cost‐effective with comparable perioperative outcomes. The technical aspects elucidate the role of intraoperative CEUS to facilitate and ascertain selective ischaemia. Further work is required to demonstrate long‐term oncological outcomes. © 2016 The Authors. The International Journal of Medical Robotics and Computer Assisted Surgery published by John Wiley & Sons, Ltd.